Electrical conductivity and dielectric and ferroelectric properties of chromium doped lead zirconate titanate ceramic - P. Ketsuwan (2018)
In this study, the influence of the addition of chromium (Cr3+) of 0.1-3 mol% on electrical conductivity, dielectric and ferroelectric properties of the morphotropic lead zirconate titanate (Pb(Zr0.52Ti0.48)O3) ceramics has been investigated. The dielectric constant tends to slightly increase with increasing chromium concentration from 0.1-0.6 mol% while dielectric loss tends to decrease, but the trend is reversed with 1-3 mol% chromium content. In addition, the Curie temperature (TC) does not change significantly with chromium addition from 0.1-0.6 mol% but decreases significantly from 1-3 mol%. From the hysteresis loop measurement, at low concentration of Cr, the loops reveal the high value of polarization and low coercive field that refers to soft behavior while the contrary is revealed at higher Cr concentration with hard behavior. The electrical conductivity of the doped PZT ceramic measured at 50-200°C decreases with increasing chromium concentration from 0.1-0.6 mol% but increases with 1-3 mol% Cr. Copyright © Taylor & Francis Group, LLC.